Safety and tolerability of a low glycemic load dietary intervention in adults with cystic fibrosis: a pilot study - Scully, Kevin J.; Truex, Laura; Brennan, Alina; Fowler, Robert; Sawicki, Gregory S.; Uluer, Ahmet; Ludwig, David S.; Ebbeling, Cara B.; Langlais, Leah; Dziok, Angela; Freedman, Steven D.; Putman, Melissa S. (Frontiers in Nutrition, 2024)
Introduction: To achieve and maintain adequate weight, people with cystic fibrosis (CF) may often consume energy-dense, nutrient-poor foods high in added sugars and refined carbohydrates; however, little is known about the glycemic and metabolic effects of dietary composition in this patient population. The objective of this pilot study was to investigate the safety and tolerability of a low glycemic load (LGL) diet in adults with CF and abnormal glucose tolerance (AGT). Methods: Ten adults with CF and AGT completed this prospective, open-label pilot study. Mean age was 27.0±2.1 years, 64% were female, and all had pancreatic insufficiency. Each participant followed his/her typical diet for two weeks, then transitioned to a LGL diet via meal delivery service for eight weeks. The primary outcome was change in weight from baseline to study completion, with safety established if no significant decline was noted. Other key safety outcomes included change in hypoglycemia measured by patient report and continuous glucose monitoring (CGM). Exploratory outcomes included changes in other CGM measures, body composition by dual energy Xray absorptiometry (DXA), and patient reported outcomes. Results: There were no significant changes in weight or in subjectively-reported or objectively-measured hypoglycemia. Favorable non-significant non-significant changes were noted in CGM measures of hyperglycemia and glycemic variability, DXA measures of fat mass, and gastrointestinal symptom surveys. Discussion: A LGL dietary intervention was safe and well tolerated in adults with CF and AGT. These results lay the groundwork for future trials investigating the impact of low-glycemic dietary interventions on metabolic outcomes in the CF population.